2018
DOI: 10.1093/milmed/usx077
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Surgical Management of Anterior Shoulder Instability: Increased Utilization of Bone Augmentation Techniques†

Abstract: The rate of performing an arthroscopic Bankart repair has remained relatively stable as the dominant surgical procedure for shoulder instability in the military patient population. There was a significant trend of increased use of the Latarjet procedure, which likely reflects the recognition of bone loss through use of preoperative advanced imaging and computed tomography with three-dimensional reconstructions. Additionally, there was a significant decrease in adjacent superior labrum anterior/posterior repair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…3 Epidemiological studies have shown a significant increased use of the Latarjet procedure over recent years. 6 This likely represents the better recognition of bone loss through improved computed tomography with 3-dimensional reconstructions.…”
Section: Surgical Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Epidemiological studies have shown a significant increased use of the Latarjet procedure over recent years. 6 This likely represents the better recognition of bone loss through improved computed tomography with 3-dimensional reconstructions.…”
Section: Surgical Managementmentioning
confidence: 99%
“…Although anterior arthroscopic stabilisation (capsulolabral repair) may have become the gold standard for the first time dislocator, there is a significant trend toward increased bone augmentation surgery with evolving indications. 6 Primary arthroscopic Bankart repair has proven to be a successful operation. 7e10 However more recently 'critical' anteroinferior bone loss, 'off track' Hill-Sachs lesions, contact sports, overhead athletes and inferior shoulder hyperlaxity have been identified as risk factors associated with failure.…”
Section: Anterior Bone Block Proceduresmentioning
confidence: 99%
“…From 2004-2013, the overall annual incidence of both arthroscopic stabilization and boneblock procedures increased; however, the proportion of stabilization cases using bone-block augmentation increased significantly, while the proportion of arthroscopic stabilizations decreased significantly. In a recent study of the military population, Galvin et al 49 reported that although arthroscopic Bankart repair remained relatively stable as the dominant surgical procedure for ASI, there was a significant increase in the use of the Latarjet procedure, probably because of the recognition of bone loss through use of preoperative advanced imaging and 3-dimensional reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of the military population, Galvin et al. 49 reported that although arthroscopic Bankart repair remained relatively stable as the dominant surgical procedure for ASI, there was a significant increase in the use of the Latarjet procedure, probably because of the recognition of bone loss through use of preoperative advanced imaging and 3-dimensional reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…2,7,13 With increasing knowledge and recognition of bone loss in treating anterior shoulder instability, there has been a noted increase in the number of bone-block stabilization procedures being performed for the treatment of shoulder instability in the United States. 6,9 Regardless of the technique or strategy used to treat anterior shoulder instability, the role of postoperative rehabilitation is critical in achieving functional stability and appropriate return to activity. 4,5,8 Nonetheless, there is a paucity of high-quality evidence investigating the effect of rehabilitation programs on functional outcomes after both arthroscopic and open stabilization procedures.…”
mentioning
confidence: 99%